2022
DOI: 10.1021/acs.orglett.2c00566
|View full text |Cite
|
Sign up to set email alerts
|

Photoacid-Enabled Synthesis of Indanes via Formal [3 + 2] Cycloaddition of Benzyl Alcohols with Olefins

Abstract: An environmentally friendly and highly diastereoselective method for synthesizing indanes has been developed via a metastable-state photoacid system containing catalytic protonated merocyanine (MEH). Under visible-light irradiation, MEH yields a metastable spiro structure and liberated protons, which facilitates the formation of carbocations from benzyl alcohols, thus delivering diverse molecules in the presence of various nucleophiles. Mainly, a variety of indanes could be easily obtained from benzyl alcohols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Then, by reacting with another molecular formaldehyde via the dominant transition state TS1 , trans - 7 was produced, while cis - 7 resulting from the disfavored transition state TS2 was not detected. Alternatively, both products 11a and 11b could be generated simultaneously through further protonation ring-opening/FC reactions of trans - 7a and 7b , as well as through the direct FC reaction of i (when strong EDGs were present in Ar 1 ) [ 22 , 23 ].
Scheme 3 Proposed mechanism for the formation of 7 and 11
…”
Section: Resultsmentioning
confidence: 99%
“…Then, by reacting with another molecular formaldehyde via the dominant transition state TS1 , trans - 7 was produced, while cis - 7 resulting from the disfavored transition state TS2 was not detected. Alternatively, both products 11a and 11b could be generated simultaneously through further protonation ring-opening/FC reactions of trans - 7a and 7b , as well as through the direct FC reaction of i (when strong EDGs were present in Ar 1 ) [ 22 , 23 ].
Scheme 3 Proposed mechanism for the formation of 7 and 11
…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the Lewis and Bro̷nsted acid-mediated reports for synthesizing indene and indane derivatives have also been known in the literature. For example, in 2013, the synthesis of substituted indenes via FeCl 3 -mediated intramolecular cyclization reaction of allylic tert -alcohol was uncovered by Dethe et al, as depicted in Scheme a; and the same research group in 2013 also reported FeCl 3 -promoted synthesis of indene derivatives starting from diene esters (Scheme b); on the other hand, recently, in 2021, Balamurugan et al demonstrated the synthesis of indanes from the ortho -alkenyl benzaldehydes, N -protected indoles, and trimethyl orthoformate in the presence of the catalytic amount of TfOH (Scheme c); in 2022, Liu and his coworkers communicated the photoacid-induced prescribed [3 + 2] cycloaddition of olefins and benzyl alcohols (Scheme d). Though a number of efficient reports exist in the literature, there would still be various possible ways to synthesize indene derivatives using well-organized and effective one-pot procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the wide-ranging naturally occurring synthetic, biological, and pharmacological significances of indene/indane skeletons, in the recent past, many research groups paid attention to developing simple, novel, and efficient routes to synthesize substituted indenes and indanes. , In this context, recently, the C–H bond activation followed by cyclization pathways for the indene derivatives has been reported independently by the research groups of Dethe, Kuninobu, and Muralirajan . Also, recently the research groups of Murai, Friedfeld, and Bhunia individually disclosed the inter/intramolecular transition metal-catalyzed cyclization routes to synthesize indenes.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Later, Wang and co-workers explored glycosylation by using Eosin Y and other photoacid catalysts. [15] Since then, there have been a few excellent reports on the use of photoacids in Friedel-Craft's arylation of carbonyls, [16] acetal formation, [17] Minisci-type acylation of N-heteroarenes, [18] indane synthesis, [19] hydrodesulfurization of aryl thioethers [20] and glycosylation. [21] Structurally speaking, mostly, thioureas have been utilized as photoacids.…”
Section: Introductionmentioning
confidence: 99%